(untitled) (Dermatology Reports, 2021)
Langerhans cell histiocytosis (LCH) is an idiopathic group of disorders characterized histologically by proliferation and infiltration of tissue by Langerhans cell-type histiocytes. This disease can affect various organs. Patients with single system lesion should be followed carefully. Detection of somatic BRAF-V600E mutation in circulating blood cells or in lesional biopsies has been associated with high-risk clinical characteristics. A 38-year old male presented to our Dermatology Centre with a 3 months history of small nodule on his right leg skin. Surgery to remove the lesion was performed. The diagnosis of skin-limited Langerhans cell histiocytosis was established. Due to possible systemic spread the patient was referred to a haematologist for further evaluation. Full body CT scan did not show any infiltrates in other organs. Bone marrow aspirate and biopsy was performed, no Langerhans cells were detected. Sometimes skin lesions may represent the most clinically evident manifestation of potentially life-threatening multisystem disease.